2017
DOI: 10.21065/1920-4159.1000232
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Flavone Analogues

Abstract: Background: Most of the available antimicrobial drugs have developed resistance; some of them suffer from severe toxicity, side effects. So, there is a need to discover novel compound(s) which should not only be potent, but also less toxic and cost effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Extensive biological studies of flavonoids have revealed their health benefits including disease prevention [5,72]. They have exhibited anti-oxidant, anti-inflammatory, antibacterial, and anti-viral activities [73], anti-oxidant [74], anti-allergic anti-carcinogenic properties [75]. The protective effects of flavonoids have been reported as they help to reduce oxidative stress in the body.…”
Section: Health Benefits Of Flavonoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive biological studies of flavonoids have revealed their health benefits including disease prevention [5,72]. They have exhibited anti-oxidant, anti-inflammatory, antibacterial, and anti-viral activities [73], anti-oxidant [74], anti-allergic anti-carcinogenic properties [75]. The protective effects of flavonoids have been reported as they help to reduce oxidative stress in the body.…”
Section: Health Benefits Of Flavonoidsmentioning
confidence: 99%
“…The flavonoids, 3-hydroxy flavone derivatives, and 3-methyl flavanone showed activity against Gram +ve bacteria [75]. Scandenone, kaempferol-3,7-O-α-L-dirhamnoside tiliroside, quercetin-3,7-O-α-L-dirhamnoside showed anti-microbial activity [43].…”
Section: Anti-microbial Activitymentioning
confidence: 99%